Antioxidant status of one-year-old carp infected with Eudiplozoon nipponicum and the effects of corrective factors - O. V. Fedorovych; B. B. Saiuk; B. V. Gutyj; M. P. Drach; T. V. Martyshuk; S. I. Kravets; A. O. Boiko; U. M. Vus; O. Ye. Vozna; Kh. Ya. Leskiv; V. Ya. Momut (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
One of the least studied monogeneosis diseases to date is carp diplostomosis. Outbreaks of this disease have been increasingly reported in fish farms in the western region of Ukraine. Moreover, this parasite is most commonly found in larger quantities in young fish. The aim of this study was to investigate the effect of the drug “Brovermectin-Granulat™” and ground milk thistle fruits on the levels of lipid peroxidation products and the activity of the enzymatic component of the antioxidant defense system in the hepatopancreas of one-year-old scale carp infected with Eudiplozoon nipponicum. The research was conducted in the pond fish farms of the State Enterprise “Rybgosp “Halytsky” (now LLC “Rybgosp “Burshtynskyi”) in the Rohatyn district of Ivano-Frankivsk region and in the private farm “Dobrotvirskyi fish factory” in the Kamyanka-Buzka district of Lviv region, located in the warm waters of cooling ponds of the Burshtyn and Dobrotvir thermal power plants. One-year-old scale carp (with a body weight of 45–47 g), infected with Eudiplozoon nipponicum, were selected for the study. To examine the effects of “Brovermectin-Granulat™” and milk thistle fruits on lipid peroxidation products and the antioxidant system enzymes in the hepatopancreas, we formed three groups of fish, with 6 specimens in each group: a control group – fish infected with monogeneans, an experimental group I – fish treated with the antiparasitic drug “Brovermectin-Granulat™” (at a dose of 60 mg/kg body weight), experimental group II – fish treated with “Brovermectin-Granulat™” (at a dose of 60 mg/kg body weight) and ground milk thistle fruits (5 % of the compound feed was supplemented with ground milk thistle fruits by granulation). The study of peroxide processes and the antioxidant system status in the hepatopancreas of one-year-old scale carp infected with Eudiplozoon nipponicum, and after the application of the above-mentioned drugs, showed that in the experimental groups of fish, a reduction in the levels of lipid peroxidation products was observed. It was also noted that the studied supplement based on ground milk thistle fruits had a stimulating effect on the antioxidant status of the fish, as evidenced by significantly higher activity of catalase, superoxide dismutase, and glutathione peroxidase in the hepatopancreas of the experimental fish.